A closure model for predicting crack growth under creep-fatigue loading. (August 2019) - Potirniche, Gabriel P.
Highlights: Hold time during creep-fatigue loading decreases plasticity-induced crack closure. Hold time increases crack surface displacements and reduces crack opening stresses. Longer creep hold times lead to faster crack growth rates during cyclic loading. Hold time effect on crack closure highlights the interaction of creep and fatigue. Abstract: A strip-yield model was formulated to simulate creep-fatigue crack growth and to quantify the influence of hold time on plasticity-induced crack closure during creep-fatigue crack growth. Creep-fatigue experiments have shown that longer creep hold times result in faster crack growth rates in subsequent fatigue cycles. This model advances the idea that a decrease of plasticity-induced crack closure is experienced by the crack during fatigue loading when a longer hold time is applied each creep-fatigue cycle. Consequently, the crack tip experiences an increase in the effective stress intensity factor range causing faster growth rate during the fatigue loading. The weight function method was used to compute stress intensity factors and surface displacements for cracks embedded in a material experiencing elastic, plastic and creep deformations at elevated temperatures. It is shown that the longer the hold time, the larger the creep deformation and crack opening displacements in the near crack-tip region. In turn, this leads to a decrease in the crack-tip opening stress/load and faster crack growth rates during the subsequent fatigue cycle. The model was used to perform simulations of creep-fatigue crack growth at elevated temperatures in a nickel-base superalloy and AISI 316 austenitic steel.